A teacher's guide to successful classroom management and differentiated instruction - Birnie, Billie F. (Wrinkles in teaching, 2017)
This book is a practical, straightforward conversation with teachers about two key aspects of their work. Illustrating concepts with examples from both elementary and secondary classrooms, the guide also offers strategies, checklists, and activities to help teachers improve their practice.